Short communication: (What) To teach or not to teach – that is the question. Issue 4 (9th February 2016) - Santamarina, Juan Carlos
Abstract : There has been an explosion of knowledge in geotechnical engineering, yet the art and science paradigm remains deeply rooted in the field. Geotechnical engineering students will face today's prevailing difficulties as well as new and demanding geotechnical challenges such as those associated with energy and the environment. Confronting these situations and needs requires a sound and resourceful foundation. Therefore, geotechnical engineering teachers must review their educational programmes ( a ) to reconsider the role of empiricism, ( b ) to prune incorrect concepts and biases (e.g., enduring misnomers, incorrect explanations, superseded graphical approaches, unsound tricks and fragile correlations, and education based on extremes (dry–saturated, clay–sand, drained–undrained)), and ( c ) to promote a careful understanding of fundamentals (e.g., the particulate nature of soils and fractured rocks, formation history, the essential relevance of effective stress, thermo-hydro-chemo-mechanical coupled processes, repetitive loads and ubiquitous localisations). Finally, they must continue reflecting on the role of the engineer in society, within an ever-changing world as the driver for innovation.